Horticultural Trends and Urban Agriculture Resilience in Malang: A Five-Year Statistical Analysis - Indriani, Tantri Indriani (PANGRIPTA, 2025)
Urban horticulture plays a strategic role in strengthening sustainable food systems amid the rapid expansion of urban areas. In Indonesia, secondary cities like Malang are experiencing land-use transformations that marginalize agricultural activities, including horticulture. This study explores the dynamics of horticultural production in Malang Municipality from 2019 to 2023, utilizing primary data from the Horticulture Statistics Report published by the Malang City Statistics Agency (BPS). The analysis focuses on four major commodity groups: seasonal fruits and vegetables (SBS), annual fruits and vegetables (BST), biopharmaceutical crops (TBF), and decorative plants (TH). The findings indicate significant fluctuations in both harvested area and production levels, particularly in seasonal crops such as oyster mushrooms and chili peppers, which are highly sensitive to market prices and climate variability. Annual fruits like mango and rambutan consistently dominated the production volume, while biofarmaka crops such as turmeric and ginger showed a worrying downward trend. Notably, lemon production surged by over 1,100% between 2022 and 2023, suggesting new patterns of local market demand. Meanwhile, the decorative plant sector remained relatively stable, reflecting its niche role in urban aesthetic and cultural practices. These patterns reveal both the vulnerability and potential of urban horticulture within the broader framework of urban resilience and land governance. The study advocates for integrated urban agricultural planning, local value-chain strengthening, and policy support to ensure the viability of horticulture as part of sustainable urban development in Indonesian cities.